Pengaruh E-Service Quality Terhadap Loyalitas Pelanggan Grabfood Di Kabupaten Lamongan - Pretty Alfina; Yudhi Prasetya Mada (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to analyze the effect of E-Service Quality on Customer Loyalty of GrabFood Service Feature Users (Study on GrabFood Customers in Lamongan City). The sample that has been used in this study was 100 respondents using purposive sampling technique. The data has been analyzed using SPSS with SPSS 26 software. The results of the study show that partially there is a significant effect of the E-Service Quality variable on the loyalty of the Lamongan City GrabFood customers, simultaneously the E-Service Quality variable, both have a significant effect on the Lamongan City GrabFood Customer loyalty